2013
DOI: 10.1111/fcp.12057
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents angiotensin II‐induced endothelial dysfunction in rabbit aorta via activating HGF/Met system and PPARγ pathway

Abstract: Telmisartan with partial activation of peroxisome proliferator-activated receptor γ (PPARγ) powerfully reduces blood pressure, improves endothelial function and lipid metabolism. Hepatocyte growth factor/mesenchymal-epithelial transition factor (HGF/Met) system in the local vasculature plays a pivotal role in maintaining normal endothelial function. This study is aimed to evaluate whether telmisartan directly prevents angiotensin II (Ang II)-induced endothelial dysfunction (ED) via activating HGF/Met system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Ang II enhances the secretion of ET, reactive oxygen species, and inhibits the expression of NO eNOS in endothelial cells . Recent studies have confirmed that incubation with Ang II in vitro can directly induce endothelial dysfunction …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Ang II enhances the secretion of ET, reactive oxygen species, and inhibits the expression of NO eNOS in endothelial cells . Recent studies have confirmed that incubation with Ang II in vitro can directly induce endothelial dysfunction …”
Section: Discussionmentioning
confidence: 94%
“…Li et al demonstrated that TMST alleviated pulmonary artery endothelial dysfunction induced by monocrotaline through a PPARγ‐dependent phosphoinositide 3‐kinase/Akt/eNOS pathway. Hu et al has found that TMST improves Ang II endothelial dysfunction by activating HGF/Met system and PPARγ pathway. However, little information is available whether TMST can prevent endothelial dysfunction in CSFP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In numerous respects, angiotensin II and natriuretic peptides may be considered physiological antagonists for each other, and the two peptide systems exert opposing effects on blood pressure and sodium conservation . At the level of the VSMC, ANP inhibits cell contraction and growth, while angiotensin II promotes them.…”
Section: Introductionmentioning
confidence: 99%